2007
DOI: 10.1080/02699050701481613
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effects of a dynamic lycra® orthosis on arm function in a late stage patient with acquired brain injury

Abstract: The findings suggest that a lycra orthosis may have some beneficial effects on upper limb function late after brain injury. Results were however equivocal, suggesting (a) that effect mechanisms may be quite complex and (b) that future evaluations may require careful construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 33 publications
0
37
0
2
Order By: Relevance
“…A single case study on a patient with acquired brain injury who wore a sleeve for 18 weeks reported improvements in the upper limb active range of movement, self-rated function and one component of a writing test, with some suggestion of a carry-over effect when treatment was withdrawn. 12 Similarly, a small (n=16) cross-over study on people with post-stroke hemiplegia reported that a Lycra sleeve (from the wrist to the middle of the arm) worn over 3 hours period, improved wrist posture, reduced wrist and finger flexor spasticity and a mean (4.1°±13.0°) increase in passive range of movement at the shoulder joint (across all movements). 10 These effects were significantly different when compared to patients not wearing the sleeve.…”
Section: Introductionmentioning
confidence: 99%
“…A single case study on a patient with acquired brain injury who wore a sleeve for 18 weeks reported improvements in the upper limb active range of movement, self-rated function and one component of a writing test, with some suggestion of a carry-over effect when treatment was withdrawn. 12 Similarly, a small (n=16) cross-over study on people with post-stroke hemiplegia reported that a Lycra sleeve (from the wrist to the middle of the arm) worn over 3 hours period, improved wrist posture, reduced wrist and finger flexor spasticity and a mean (4.1°±13.0°) increase in passive range of movement at the shoulder joint (across all movements). 10 These effects were significantly different when compared to patients not wearing the sleeve.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the literature, findings particularly for these three aims have shown conflicting and inconclusive evidence on efficacy. [5,[9][10][11][12][14][15]23] On the other hand, some of the secondary aims like enhancing functional independence and reducing pain that have presented some positive findings in the literature [10,14,15] were not significantly associated with the therapists' perception of splint efficacy. This therapists' focus on reducing impairments and not improving the clients' much valued functional independence questions the clientcentered practice of OTs.…”
Section: Discussionmentioning
confidence: 96%
“…[4,[6][7][8] However, splinting for post-stroke spasticity and contractures is contentious and debate continues unabated due to insufficient evidence unambiguously documenting its effectiveness. [9,10] Recent literature has determined splinting to be effective in some clinical situations [5,[9][10][11][12][13] (example, shorter daily splinting time, use of dynamic lycra splint), but ineffective in others. [6,14,15] However, most of these studies have been critiqued for their methodological limitations, which has undermined their findings somewhat.…”
Section: Introductionmentioning
confidence: 99%
“…Around 22% of CP cases present with spastic diplegia of varying severity, often influencing the child's gait. 2 Orthotic intervention is well documented for this subject group. 1 Dynamic elastomeric fabric orthoses (DEFOs) have been used internationally since the early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that these orthoses exert a paratonic torsional and compressive effect to positively influence alignment, biomechanics and neuromuscular activity. 2 There is a growing body of literature contributing to evidence of their effectiveness: A recently conducted literature review covering the period 1993-2008 identified seven case-controlled studies, 12 single case studies and two MSc research theses. 3 Improvements in function, range of movement and thoracic stability, [3][4][5] as well as dynamic musculoskeletal correction, 6,7 have all been reported.…”
Section: Introductionmentioning
confidence: 99%